Impact of interface orientation on magnetic coupling in highly ordered systems: a case study of the low-indexed Fe3O4/NiO interfaces - Krug, Ingo Peter; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2008)
We investigated the influence of the interface orientation on the magnetic coupling for the (110), (001), and (111) interfaces of epitaxial NiO thin films on single-crystal Fe3O4. In our analysis, we combine magnetic x-ray spectroscopies with circularly and linearly polarized light, i.e., x-ray magnetic circular and linear dichroism (XMCD and XMLD). A full treatment of the anisotropic XMLD in single-crystalline materials backed by theoretical support allows for a reliable vectorial magnetometry. Both the (110) and the (111) interfaces produce collinear coupling, which at first glance contradicts Koon’s theory, while at the (001) interface, a perpendicular (spin-flop) coupling between a ferrimagnet and an antiferromagnet is observed. Furthermore, we find a pronounced enhancement of the interfacial uncompensated magnetization for the (110) interface only, while for the two other interfaces this value is considerably lower. These apparent discrepancies are resolved in terms of a detailed consideration of exchange and magnetoelastic effects for the individual orientations. The results highlight the fundamental role of the crystalline interface orientation in magnetic coupling phenomena involving oxidic systems.